Dermatologist demographics and patient satisfaction: A single-center survey study - Mio Nakamura, MD; Naomi F. Briones, MD; Thy Thy Do, MD; Mick P. Couper, PhD; Kelly B. Cha, MD (Wolters Kluwer, 2020)
Background: Patient satisfaction is a proxy for quality clinical care. Understanding the factors that drive patient satisfaction scores is important because they are publicly reported, may be used in determining hospital and physician compensation, and may allow patients to preselect physicians. Objective: This single-center survey study of adult patients at the Michigan Medicine outpatient dermatology clinics aimed to investigate how patients respond differently to theoretical dermatologic scenarios with varying dermatologist gender. Methods: Each questionnaire contained one of four clinical scenarios illustrating overall positive or negative encounters with a male or female dermatologist, followed by questions derived from the Press Ganey survey to assess patient satisfaction. Results: A total of 452 completed questionnaires were collected. There were statistically significant differences in overall patient satisfaction scores between positive versus negative female and positive versus negative male dermatologists, but there were no differences in scores between positive female and positive male dermatologists or between negative female and negative male dermatologists. There were also no differences in overall scores after controlling for patient demographic characteristics or patient-dermatologist gender concordance. Conclusion: Previous studies have suggested that male physicians receive better patient satisfaction scores compared to female physicians. However, our study found that, in response to hypothetical scenarios of positive and negative dermatology encounters, dermatologist gender did not affect any domain of patient satisfaction scores. Limitations include the use of hypothetical patient-dermatologist encounters and possible lack of generalizability because the study was conducted at one academic center in southeast Michigan with a predominantly Caucasian patient population.